2020
DOI: 10.3389/fimmu.2020.566309
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Innate Immune Memory by Engineered Nanoparticles in Monocytes/Macrophages: From Hypothesis to Reality

Abstract: The capacity of engineered nanoparticles to activate cells of the innate immune system, in particular monocytes and macrophages, is considered at the basis of their toxic/inflammatory effects. It is, however, evident that even nanoparticles that do not directly induce inflammatory activation, and are therefore considered as safe, can nevertheless induce epigenetic modifications and affect metabolic pathways in monocytes and macrophages. Since epigenetic and metabolic changes are the main mechanisms of innate m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 113 publications
(123 reference statements)
3
15
0
Order By: Relevance
“…While it is now clear that many NPs do not have the capacity for activating human monocytes if they are endotoxin-free [ 12 , 13 , 35 , 36 , 39 ], some data point to the possibility that they can prime monocytes and induce innate memory, which then changes the secondary reaction of cells to a subsequent stimulation [ 28 , 29 , 30 , 31 , 32 ]. We have examined the capacity of AuNPs to induce innate memory in monocytes from six different donors in 2D and 3D cultures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While it is now clear that many NPs do not have the capacity for activating human monocytes if they are endotoxin-free [ 12 , 13 , 35 , 36 , 39 ], some data point to the possibility that they can prime monocytes and induce innate memory, which then changes the secondary reaction of cells to a subsequent stimulation [ 28 , 29 , 30 , 31 , 32 ]. We have examined the capacity of AuNPs to induce innate memory in monocytes from six different donors in 2D and 3D cultures.…”
Section: Discussionmentioning
confidence: 99%
“…While our understanding of innate memory is still largely incomplete, it is tempting to speculate that engineered NPs might be used for a targeted reprogramming of innate immunity for preventive and therapeutic scopes, such as in vaccination and immunotherapy [ 24 , 25 , 26 , 27 ]. Few recent studies show that indeed NPs may prime human monocytes and vertebrate/invertebrate macrophages and induce a modification of their response to a subsequent inflammatory challenge [ 28 , 29 , 30 , 31 , 32 ]. In this study, we have examined the memory-inducing capacity of AuNPs on human primary monocytes to define the most suitable conditions for a realistic evaluation.…”
Section: Introductionmentioning
confidence: 99%
“…The present study did not yet address the mechanisms underlying the observed memory effects (studies currently ongoing), which is an issue of particular interest since the observed effects were different (increased vs. decreased production) depending on the cytokine under evaluation, implying concomitant changes at different levels, likely including epigenetic and metabolic regulation [ 51 , 52 , 53 , 54 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary results indeed show that the memory response of human primary monocytes primed with live BCG and challenged with LPS, in terms of production of inflammatory TNFα and IL-6 and anti-inflammatory IL-1Ra and IL-10 cytokines was significantly reduced if Au NPs were present with BCG during priming [ 59 ]. These findings open the possibility of novel approaches of immunomodulation, in which NPs can be used for improving vaccine efficacy and general resistance to infections, and also for modulating and rebalancing the altered immune responses in a range of immune-related diseases, such as chronic inflammatory, degenerative, and autoimmune diseases [ 152 ].…”
Section: The Long-term Effects Of Np Exposurementioning
confidence: 99%